ANALISIS BENTUK LAGU NAWWARTIL AYYAM GRUP MUSIK GAMBUS EL-FAIRUZ DI KOTA MEDAN - Reza, Nanda; Mukhlis; Hirza, Herna (Jurnal Penelitian Musik, 2021)
This study aims to determine the form of the song Nawwartil Ayyam by the El-Fairuz gambus music group in Medan. This research is based on a theoretical basis that explains the form of songs. The research method used is descriptive qualitative which includes several aspects, namely observation, interviews, documentation, and literature study. The population in this study were the El-Fairuz gambus music artists. The research results attest are analysis form of the Nawwartil Ayyam song played with allegretto = 110 and Am = La as the basic tone. Consists of 66 bars. Time signature 4/4 (bar 1 until 43 and 45until 66) and time signature 2/4 at bar 44. Be found 4 sentence of 11 phrase with repetition and 14 motive witgh repetition too.